HILOLDOSHLAR OILASI TAVSIFI VA SISTEMATIKASI. TARQALISHI VA AHAMIYATI. (Ta'limning zamonaviy transformatsiyasi, 2024)
Аннотация: В данной работате представлена информация о семействе полумесяцев , их видах и родах, распространенных представителях по всей земле и их значении. Annotation: This thesis describes the family of hillocks ,their species and order , their representatives that are common throughout the Earth, and their importance.